Photoinduced changes of the optical parameters of thin films from Ge30.8As5.7S63.5 glass - Yakuphanoğlu, Fahrettin; Arsova, D.; Vateva, E. (Natl Inst Optoelectronics, 2007)
Extremely high irreversible changes of the optical parameters have been found after long time illumination of thin films thermally evaporated from Ge30.8As57S63.5 glass, which belongs to the Ge2As3-AsS3 line. Illumination of virgin films leads to a blue shift of the absorption edge, photo-bleaching (PB). Changes of the optical band gap, E-g up to about 600 meV (similar to 27%), of the refractive index, n up to 0.2 (similar to 9.5%), as well as the thickness increase similar to 70 nm (11%) have been obtained. The dependences of the parameters of the irreversible PB on the film thickness (between 0.4 - 1.4 mu m) and the time of illumination (up to 3h) have been investigated. The magnitude of the irreversible PB is compared with that of the irreversible thermo-bleaching after annealing near to the glass transition temperature, as well as with that of the reversible photo-darkening of the annealed films. The reasons for the appearance of such high photo-induced changes, which are interesting for practical uses, are discussed.
14th International School on Condensed Matter Physics -- SEP 17-22, 2006 -- Varna, BULGARIA
Keywords: chalcogenide films; refractive index; optical band gap